Fly Ash as Low Cost Adsorbent to Remove Dyes (International Journal of Scientific Research and Management (IJSRM), 2014)
: Fly ash, a residue from thermal power plant, is a waste material. It was investigated as new alternative low cost adsorbent to lower methylene blue dye concentration from synthetic waste stream which represent textile wastewater. Potential of adsorbent was identified by doing characterization. Before using fly ash as adsorbent, it was physically activated. Activation process is described in upcoming section. Wastewater stream was prepared synthetically to create artificial actual scenario.In the present study, studies were conducted as a function of adsorbent dosage, temperature, concentration dosage, and pH on adsorption process. We found that, there is no considerable effect of temperature on adsorption. We only check for Freuindlich adsorption isotherm. As regression co-efficient is 0.8351, we can’t say that all adsorption data is well fitted in this isotherm model.